Socioeconomic determinants of modern climate change adaptation of small-scale vegetable farmers in Bohlabela District, Mpumalanga Province - Maiwashe Tagwi, Aluwani; Khoza, Khensani Nicolene (Frontiers in Climate, 2024)
Climate change has a significant impact on the community's small-scale agriculture. Small-scale farmers' ability to effectively adjust to climate change is severely limited. The challenge is made worse by the lack of use of advanced science and technology. Small-scale agriculture is an integral part of Mpumalanga province's economic activities. The study looked at factors affecting small-scale farmers' modern climate change adaptation. The representative sample size of 244 small-scale crop farmers was used from four villages. The research used face-to-face interviews using a semi-structured questionnaire. The factors associated with climate change adaptation were analysed using the Logistic regression model. The results of the model indicated that factors associated with modern climate change adaptation were farm association membership, access to extension services, theft, and animal trespassing in the farming plots. It was recommended that training be made available to expose farmers to the causes of climate change and mitigation strategies in general. It was recommended that the government must expand the disaster management budget for farmers as most farmers had reported having experienced climate change disasters but with no financial help extended. The study recommended that government must encourage farmers to participate in farm associations, extension services budget must be increased to ensure that each farmer can access an extension officer once or twice a year. Another recommendation was that the government must strengthen community policing in farming areas to address theft. It also recommended that the problem of animal trespassing be resolved by creating guidelines that all community members must abide by.